The smart circular economy: A digital-enabled circular strategies framework for manufacturing companies - Kristoffersen, Eivind; Blomsma, Fenna; Mikalef, Patrick; Li, Jingyue (Journal of business research, 2020)
•Novel framework to align activities across information systems and the circular economy.•Digital circular economy research agenda and implications for practitioners.•Guidance for aligning digital and sustainable strategies.•Knowledge base of 100 theorized and real-world smart circular strategies.•Digital circular economy as a cornerstone of a sustainable society. Digital technologies (DTs), such as the Internet of Things (IoT), big data, and data analytics, are considered essential enablers of the circular economy (CE). However, as both CE and DTs are emerging fields, there exists little systematic guidance on how DTs can be applied to capture the full potential of circular strategies for improving resource efficiency and productivity. Furthermore, there is little insight into the supporting business analytics (BA) capabilities required to accomplish this. To address this gap, this paper conducts a theory- and practice-based review, resulting in the Smart CE framework that supports translating the circular strategies central to the goals of manufacturing companies in contributing the United Nation’s (UN) 12th Sustainable Development Goal, that is, “sustainable consumption and production,” into the BA requirements of DTs. Both scholars and practitioners may find the framework useful to (1) create a common language for aligning activities across the boundaries of disciplines such as information systems and the CE body of knowledge, and (2) identify the gap between the current and entailed BA requirements and identify the strategic initiatives needed to close it. Additionally, the framework is used to organize a database of case examples to identify some best practices related to specific smart circular strategies.